Penyelesaian Penanganan Perkara Tindak Pidana Penyalahgunaan Narkotika - Adoa, Rama; Sopacua, Margie Gladies; Taufik, Iqbal (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: So far, rehabilitation sentences have been imposed for narcotics abuse through the mechanism of examination in court and through a judge's decision or judge's decision based on a Supreme Court Circular.Purposes of the Research: This writing aims to examine and analyze the Implementation of the Prosecutor's Dominus Litis Principle in Completing the Handling of Narcotics Abuse Crime Cases and the Obstacles Faced in the Implementation of the Prosecutor's Dominus Litis Principle in Completing the Handling of Narcotics Abuse Crime Cases.Methods of the Research: The type of research in this research is empirical juridical, in other words, it is a type of sociological legal research and can also be called field research, which examines the legal provisions that apply and what actually happens in society. Supporting data and information are then identified and then systematized for interpretation and given arguments to draw conclusions on the problem.Results of the Research: The results of this study indicate that the implementation of the prosecutor's dominus litis principle in completing the handling of cases of criminal acts of narcotics abuse at the Ambon District Attorney's Office, that the implementation of the Attorney General's Guidelines Number 18 of 2021 cannot be applied. From an internal point of view, the Attorney General's Office prefers to proceed with the prosecution stage for several existing narcotics cases. The obstacles faced in implementing the principle of Dominus Litis Prosecutors in completing the handling of cases of criminal acts of narcotics abuse at the Ambon District Attorney. Which led to JA Guideline No. 18 and No. 11 has not been implemented at the Ambon District Attorney.